Kommunalspezifische Nachhaltigkeitssteuerung. Erfahrungen und Empfehlungen. - Kirst, Ev; Lang, Daniel J.; Heinrichs, Harald; Plawitzki, Jule (Oekom, 2019)
Kommunalverwaltungen stehen vor der Herausforderung, Nachhaltigkeit ganzheitlich in Verwaltungsaufbau und -abläufe zu integrieren. Unser Ansatz zur kommunalspezifischen Nachhaltigkeitssteuerung wurde in zwei deutschen Städten entwickelt. Er beschreibt, welche Handlungsoptionen es gibt und wie Verwaltungen die zu ihrer Gemeinde und Situation passenden auswählen können.

Local government plays an important role in operationalizing and implementing the United Nation's Sustainable Development Goals. To reach these goals, local administrations, as key stakeholders, should be promoted. Despite numerous promising attempts and approaches, public administrations still face great challenges in integrating sustainability goals into their actions. In this article, we present an approach for developing a municipality-specific form of sustainability management. This focuses on 14 key areas and involves a five-step procedure for successful implementation. Based on the results of two case studies in the German cities of Freiburg im Breisgau and Hansestadt Lüneburg, we discuss the opportunities and challenges of this approach in fostering sustainable municipalities.
Keywords: Verwaltung; Kommunalverwaltung; Nachhaltigkeit; Verwaltungsaufbau; Verwaltungsablauf; Umweltschutz; Kommunalpolitik; Umweltpolitik; Ressourcen; Leitbild; Handlungskonzept; Partizipation; Nachhaltigkeitsstrategie